Improving Student's Learning Outcomes using the Word Square Learning Model for IPS Lessons in Class V SD Negeri 040446 Kabanjahe Academic Year 2021/2022 - Jainab, Jainab; Karo Sekali, Pelista Br; Datten, Datten; Karo Sekali, Endalina Br; Ginting, Bijak (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The research carried out was classroom action research with the aim of knowing the implementation of learning, knowing mastery of learning and to determine the improvement of student learning outcomes using the Word Square learning model for Social Studies subjects in Class V SD Negeri 040446 in Kabanjahe, Karo Regency. The subject of this research is class V totaling 25 people and the object of this research is using the Word Square Model. The instruments used are observation sheets and multiple choice tests. Based on the results of this study, it was found that the implementation of learning in teacher activities was 80% good criteria, while classical completeness was 88% and learning outcomes increased 5%. Thus, this research can be concluded that, the implementation of learning criteria is good, student learning outcomes are completed and improved classically using the Word Square Model for Social Studies Subject Class V SD Negeri 040446 in Kabanjahe Academic Year 2021/2022.